2017
DOI: 10.1074/jbc.m116.753574
|View full text |Cite
|
Sign up to set email alerts
|

Cardiolipin Regulates Mitophagy through the Protein Kinase C Pathway

Abstract: Cardiolipin (CL), the signature phospholipid of mitochondrial membranes, is important for cardiovascular health, and perturbation of CL metabolism is implicated in cardiovascular disease. Although the role of CL in mitochondrial function, biogenesis, and genome stability has been studied, recent findings indicate that it is essential for functions apart from mitochondrial bioenergetics. In this study, we report that mitophagy is perturbed in CL-deficient yeast cells. Mutants of autophagy/mitophagy genes ,, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(53 citation statements)
references
References 55 publications
2
43
0
3
Order By: Relevance
“…Preservation of the integrity of the inner mitochondrial membrane is also important to sustain mitophagy. We have previously shown in swine renovascular hypertension that restoration of myocardial cardiolipin improved mitophagy [27], in agreement with the previous observation of decreased mitophagy in cardiolipin-deficient cells [56]. Therefore, pharmacological agents that target mitochondrial homeostasis might offer the prospect of decreasing hypertension related end-organ damage.…”
Section: Mechanisms Of Mitoprotectionsupporting
confidence: 85%
“…Preservation of the integrity of the inner mitochondrial membrane is also important to sustain mitophagy. We have previously shown in swine renovascular hypertension that restoration of myocardial cardiolipin improved mitophagy [27], in agreement with the previous observation of decreased mitophagy in cardiolipin-deficient cells [56]. Therefore, pharmacological agents that target mitochondrial homeostasis might offer the prospect of decreasing hypertension related end-organ damage.…”
Section: Mechanisms Of Mitoprotectionsupporting
confidence: 85%
“…It is noteworthy that the PKC family functions many signal transduction downstream, and PKCα is the predominant conventional PKC isoform expressed in mouse, rat and human heart . Furthermore, several studies have also demonstrated that mitophagy is associated with the PKC pathway . Altogether, this inspired us to explore the physical relevance between PKCα and ULK1 in PEDF‐treated OGD cardiomyocytes.…”
Section: Introductionmentioning
confidence: 99%
“…14 Furthermore, several studies have also demonstrated that mitophagy is associated with the PKC pathway. 15,16 Altogether, this inspired us to explore the physical relevance between PKCα and ULK1 in PEDF-treated OGD cardiomyocytes.…”
mentioning
confidence: 99%
“…In addition, different with the general concept that ROS is required for the inflammasome activators to induce inflammasome signaling, Lyer et al found that the oxazolidinone antibiotic linezolid, a NLRP3 agonist, activates the NLRP3 inflammasome independently of ROS, whereas mitochondrial cardiolipin is required for NLRP3 inflammasome activation [66]. Under cardiolipin deficiency, mitophagy is defective likely due to the impairment of MAPK signaling and the reduced activation of the protein kinase C pathway [67].…”
Section: Viral Targeting Of Specific Mitochondrial Moleculesmentioning
confidence: 99%